Correlating the expression levels of COBRA1 (co-factor of BRCA1) with hepatocellular carcinoma development in Egyptian patients - Kamel, Sarah (AUC Knowledge Fountain, 2013)
COBRA1 is a co-factor of BRCA1 that was identified to be the Î²-subunit of the NELF complex (Negative elongation factor) which stalls RNA polymerase II and prevents elongation of the message. The reported levels of expression of COBRA1 (NELF-B) in different types of cancers varied; COBRA1 is down-regulated in breast cancer, whereas in the upper gastrointestinal carcinomas it is up-regulated. The exact role of COBRA1 being a tumor suppressor gene or an oncogene remains unclear. To date, the levels of expression of COBRA1 in Hepatocellular Carcinomas (HCCs) are not yet tested. In an attempt to understand part of the complicated molecular events involved in the development of HCC, we collected 16 primary HCC tissues and their corresponding non-neoplastic specimens from patients undergoing either liver resection or liver transplantation. Samples were divided into two categories; those which undergone treatment prior to surgical procedure, TACE (Transarterial Chemoembolization) or radiofrequency ablation, and others that were not treated. All samples were examined at the RNA and protein levels using RT-PCR and western blotting respectively. All the results were quantified and normalized to the endogenous housekeeping gene using ImageJ software. The levels of expression were calculated relative to the expression of the corresponding non-neoplastic tissue. COBRA1 expression was tested and correlated to other molecules that were reported to be deregulated in HCC and were thought to be linked to COBRA1. These molecules were NANOG which is a marker for cell stemness; Î²-CATENIN a key player in the Wnt signaling pathway. We found that the transcript levels of COBRA1 were elevated in the entire cohort of the untreated cancer specimens when compared to the corresponding non-neoplastic tissues. The protein level of COBRA1 on the other hand, was elevated in only 6 untreated HCC specimens. The protein expressed by the NANOG and Î²-CATENIN was found to be up-regulated simultaneously with the COBRA1 in four samples. Unlike the untreated samples, treated cancer specimens displayed a decreased expression of COBRA1, NANOG and Î²-CATENIN. Our results propose COBRA1 as a novel oncogene in HCCs that may be used as a prognostic marker.